1994
DOI: 10.1177/001872089403600106
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Cooperative Problem-Solving System for En-Route Flight Planning: An Empirical Evaluation

Abstract: Both optimization techniques and expert systems technologies are popular approaches for developing tools to assist in complex problem-solving tasks. Because of the underlying complexity of many such tasks, however, the models of the world implicitly or explicitly embedded in such tools are often incomplete and the problem-solving methods fallible. The result can be "brittleness" in situations that were not anticipated by the system designers. To deal with this weakness, it has been suggested that "cooperative"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 11 publications
3
74
2
1
Order By: Relevance
“…It has been described as an unjustified assumption of satisfaction in the situation faced, although some improvements could apply (Layton et al, 1994;Parasuraman et al, 1993;Smith et al, 1997). This phenomenon is related to a low level of suspicion and is often correlated with overtrust in automation.…”
Section: Definition Of Complacencymentioning
confidence: 99%
“…It has been described as an unjustified assumption of satisfaction in the situation faced, although some improvements could apply (Layton et al, 1994;Parasuraman et al, 1993;Smith et al, 1997). This phenomenon is related to a low level of suspicion and is often correlated with overtrust in automation.…”
Section: Definition Of Complacencymentioning
confidence: 99%
“…Disuse can decrease automation benefits and lead to accidents if, for instance, safety systems and alarms are not consulted when needed. Another maladaptive attitude is automation bias [33,55,77,88,112], a user tendency to ascribe greater power and authority to automated decision aids than to other sources of advice (e.g. humans).…”
Section: Introductionmentioning
confidence: 99%
“…However, they also found that half of the participants overused the IA support by not recognizing that the IA provided a poor judgment on one trial. Similar acceptance of an incorrect automated judgment was also observed by Layton et al [91].…”
supporting
confidence: 84%
“…There may also be benefits from IA that provides an automated assessment [7], [8], [91]. Bass and Pritchett [7] found that judgment performance improved for an air traffic conflict prediction task when humans were provided with an automated assessment compared to when they were not provided with an automation assessment.…”
mentioning
confidence: 99%